Furcation Involvement Classification: A Comprehensive Review and a New System Proposal - Andrea Pilloni; Mariana A. Rojas (MDPI AG, 2018)
Various classification systems have been proposed to describe furcation lesions and Glickman’s classification for many years seems to have been the most widely utilized in the sole clinical diagnosis with no reference to the prognostic value of the lesion itself. This article reviews the previous classification systems and proposes a new method to classify furcation lesions based on the position of the gingival margin and its relationship with the furcation area (clinically exposed/non-exposed furcation area) providing significant aid for a better understanding of furcation involvements and increases the prognostic value of treatments in the long term.